Construção de competências dos profissionais dentistas em um contexto de demanda emergencial: novos protocolos após a pandemia por COVID -19 - Cristiano Santos Trindade (2023)
The present research presents as a question the identification of constituent elements for the reconfiguration of the skills of the dental professional, as organizational and strategic determinants, mobilized to carry out modified work practices through new prescriptions in the face of the covid-19 pandemic. Based on the research question, the premise of French ergonomics is adopted as a basis to support the study of work practices and routine and the objective is through qualitative and exploratory research: to map and analyze the construction of skills developed by professionals dentists, through emergency covid-19 protocols, considering the perception of dentists about carrying out their work. A determining factor in the construction of this research is the confrontation between prescribed work, understood as a task, and real work, being the activity truly carried out. To analyze real work, it is necessary to understand the task, the scientific and practical knowledge acquired by the worker and thus, through the analysis of workers' behaviors, during the exercise of their professional practice, they are analyzed through the relationship with formal work, its regulations, standards, in short, its prescription (GUÉRIN et al, 2007). The perceptions developed regarding the understanding of the worker's way of acting are linked to their ability to regulate the prescription and performance of their practical activity, being executed or modified by the worker in the act of carrying out their work (GUÉRIN, 1997; SANDBERG, 2006). However, to carry out the work, skills are mobilized and can be understood according to the perceptions about the practical work of dentists and, on the other hand, in relation to the contrasts between this practice and the new prescription (ZARIFIAN, 2003; SANDBERG, 2000; GUÉRIN , 2007). In a pandemic scenario, it is understood that the new protocols, or tasks, impacted the practical work routine of dentists, giving new meaning to their perceptions, attitudes and behaviors, regarding their own activity. In this way, the research identifies the path of building skills, through 10 emerging categories in its construct: pre-existing conceptions of the dentist about promoting safe work; transformation of the meaning of work; reorganization of strategies through decision-making in an emergency; incorporation of new activities in the performance of work; repositioning autonomy in the face of the emergency context; sharing tacit knowledge; change in communication with patients (remote communication); strategies mobilized in the face of emergency changes; competence to treat collective health and skills for new uses of tools and for incorporating new routines. Given these 10 categories, a new model for organizing dentist work emerges during the Covid-19 pandemic, resulting from the incorporation of new routines about work and its meaning, considering new protocols and prescriptions; and, about the journey of building and mobilizing your skills to carry out this work. Through this study, it is possible to understand the importance of analyzing the work of professional dentists and knowing how and what skills were built to reorganize their work in the face of the Covid-19 pandemic.